Postmortem Interval Estimation Using Accumulated Degree Days According to the Body’s Decomposition Stage - Bulut, Özgür; Bol, Semih; Akcan, Ramazan (The Bulletin of Legal Medicine, 2016)
Postmortem interval arises one of the most important research topics in worldwide modern forensic science applications. In spite of utilizing morphological, biochemical, flow-cytometric, microbiological, entomological, anthropological, spectroscopic and main postmortem changes in postmortem interval estimation, it does not seem possible to get certain results by only one test or method. Because, there are many physical, chemical and biological processes affecting the parameters. Therefore, postmortem interval estimation needs development of previous methods and implementation of novel methods. In this regard, taphonomic methods need to be improved in postmortem interval estimation and regional factors and climate impact need to be determined by experimental studies. In particular, we are of the opinion that that more accurate estimation of postmortem interval will be achieved by determining regional factor involving postmortem period. This paper aims to evaluate the relationship between postmortem interval and accumulated degree days in respect of decomposition stages. Key Words: Forensic Taphonomy, Postmortem Interval, Forensic Anthropology